The choice of surgical correction method depending on the etiology of decompensated chronic venous insufficiency - V. I. Rusyn; F. M. Pavuk; V. V. Rusyn; M. I. Borsenko (Сучасні медичні технології)
Aim. To evaluate the immediate and distant results of treatment depending on the etiology of chronic venous insufficiency in the stage of decompensation.